2011
DOI: 10.1126/science.1213841
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Confirm XMRV/MLVs in the Blood of Patients with Chronic Fatigue Syndrome: A Multi-Laboratory Study

Abstract: Murine leukemia viruses (MLV), including xenotropic-MLV-related virus (XMRV), have been controversially linked to chronic fatigue syndrome (CFS). To explore this issue in greater depth, we compiled coded replicate samples of blood from 15 subjects previously reported to be XMRV/MLV-positive (14 with CFS) and from 15 healthy donors previously determined to be negative for the viruses. These samples were distributed in a blinded fashion to nine laboratories which performed assays designed to detect XMRV/MLV nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 37 publications
5
83
1
Order By: Relevance
“…Furthermore, the absolute lack of XMRV in the various groups investigated herein challenges the results of previous studies that showed a high prevalence of XMRV in human populations and alleged an association with prostate cancer. This study supports the conclusions of studies that eventually led to the retraction of the original study reporting the association between XMRV and human diseases [19][20][21] .…”
Section: Ethical Considerationssupporting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, the absolute lack of XMRV in the various groups investigated herein challenges the results of previous studies that showed a high prevalence of XMRV in human populations and alleged an association with prostate cancer. This study supports the conclusions of studies that eventually led to the retraction of the original study reporting the association between XMRV and human diseases [19][20][21] .…”
Section: Ethical Considerationssupporting
confidence: 74%
“…The present available data led to the retraction of the original data reporting an association between XMRV and human diseases [19][20][21] . A wide variety of infectious agents, many of which are capable of infecting humans, are endemic to the Brazilian Amazon.…”
Section: Methodsmentioning
confidence: 99%
“…Although a subsequent study by a different lab identified MLV-related sequences in 86.5% of ME/CFS patient and in 6.8% of healthy controls, all but one of the viral sequences were distinct from XMRV and X-MLV and were instead more closely related to polytropic and modified polytropic MLVs (27,33,63). The preponderance of subsequent analyses, however, reported no evidence of XMRV infection in samples from patients with ME/CFS in the United States (22,29,53,55,60), the United Kingdom (13,18), Germany (24), The Netherlands (65), or China (25), and reexaminations of samples from patients previously identified as XMRV positive in the original Lombardi et al publication found no consistent evidence of XMRV infection (29,58). In addition, though XMRV infection has been proposed as a possible contributor to many other human diseases and disorders, efforts to detect the virus in samples from people with systemic lupus erythematosus (4), fibromyalgia (36), multiple sclerosis (24), amyotrophic lateral sclerosis (38), or autism (32,52) have thus far yielded negative results, and the virus has not been found in HIV-1-positive or immunosuppressed individuals or in people at high risk of infection with blood-borne pathogens (5,8,10,17,30,35,37,62).…”
mentioning
confidence: 95%
“…1 The Chronic Fatigue Initiative (CFI), a venture philanthropy organization, announced plans last week to fund epidemiological studies of CFS, build a biological database of tissues from subjects with CFS and generate hypotheses to stimulate academic research into the molecular mechanisms of the condition.…”
Section: By Lev Osherovich Senior Writermentioning
confidence: 99%